Standby extracorporeal membrane oxygenation: a better strategy for high-risk percutaneous coronary intervention - Liu, Chuang; Li, Xingxing; Li, Jun; Shen, Deliang; Sun, Qianqian; Zhao, Junjie; Zhao, Hui; Fu, Guowei (Frontiers in Medicine, 2024)
Background The incidence of cardiac arrest (CA) during percutaneous coronary intervention (PCI) is relatively rare. However, when it does occur, the mortality rate is extremely high. Extracorporeal cardiopulmonary resuscitation (ECPR) has shown promising survival rates for in-hospital cardiac arrests (IHCA), with low-flow time being an independent prognostic factor for CA. However, there is no definitive answer on how to reduce low-flow time. Methods This retrospective study, conducted at a single center, included 39 patients who underwent ECPR during PCI between January 2016 and December 2022. The patients were divided into two cohorts based on whether standby extracorporeal membrane oxygenation (ECMO) was utilized during PCI: standby ECPR (SBE) (n = 13) and extemporaneous ECPR (EE) (n = 26). We compared the 30-day mortality rates between these two cohorts and investigated factors associated with survival. Results Compared to the EE cohort, the SBE cohort showed significantly lower low-flow time (P < 0.01), ECMO operation time (P < 0.01), and a lower incidence of acute kidney injury (AKI) (P = 0.017), as well as peak lactate (P < 0.01). Stand-by ECMO was associated with improved 30-day survival (p = 0.036), while prolonged low-flow time (p = 0.004) and a higher SYNTAX II score (p = 0.062) predicted death at 30 days. Conclusions Standby ECMO can provide significant benefits for patients who undergo ECPR for CA during PCI. It is a viable option for high-risk PCI cases and may enhance the overall prognosis. The low-flow time remains a critical determinant of survival.